HIV prevalence and predictors of infection in sex-trafficked Nepalese girls and women. - Silverman, Jay G; Decker, Michele R; Gupta, Jhumka; Maheshwari, Ayonija; Willis, Brian M; Raj, Anita (JAMA : the journal of the American Medical Association, 2007)
Sex trafficking of girls and women is widespread across South Asia and is recognized as both a violent gender-based crime and major human rights violation. Inadequate empirical data exist to characterize this phenomenon and its related health consequences, such as human immunodeficiency virus (HIV) infection.
Keywords: Adolescent; Adult; Child; Female; HIV Infections; Humans; India; Nepal; Prevalence; Prostitution; Risk; Sex Offenses; Survivors